Geodemographics - Webber, Richard (Henry Stewart Talks, 2008)
Geodemographics, Different postcode examples, First assumptions, Similar neighborhoods across the country, Second assumptions, The postcode system, Mosaic UK, Postcode classification advantages, Qualifying consumption characteristics, Utilizing postcode classification, Key applications of geodemographics, Using geodemographics for insight, Political campaigning methods, Creation and meaning of a profile, Area profiling by common targets, Practical issues in customer profiling, Market estimation, Requirements of marketing GIS system, Issues when selecting a system, Neighborhood opposed to occupation, Inferences from name and address, Neighborhoods as brands, Formal test for neighborhood as a predictor, Which discriminator predicted best?, Why neighborhoods differ?, Contributors to differences in consumption, Peer group effects, Coverage of Mosaic classification systems, Similarities and differences in classification